Improving cyber security with resilience - Škanata, Dejan (2020)
Cyber security is commonly defined as the practice of protecting computers, networks, programs and data from unauthorized access or malicious attacks that are aimed for exploitation. Hence, cyber security is focused primary on malicious activities prevention and protection from occurring. Prevention and protection objectives have been usually achieved by applying traditional risk assessment and management procedures. Despite these efforts it has been shown that complete security of IT systems and data is almost impossible to achieve. Namely, by increasing number and type of different cyber threats the cyber incidents are becoming inevitable. Thus, even the strong cyber security is not enough anymore. Because of that organizations need to build the cyber resilience which mainly deals with system respond and recovery after disruptive event occurring. Cyber security combined with cyber resilience opens a new perspective towards better overall security of IT systems.
Bibliografske bilješke na kraju teksta ; bibliografija: str. 8-9.
Abstract.
Keywords: Cyber sigurnost -- Informacijski sustavi -- Upravljanje rizicima